(untitled) (Eurasian Journal of Engineering and Technology, 2023)
This article deals with the problem of air pollution at the present stage. The issues of atmospheric air pollution and the health of the population associated with it have been studied. Also, an analysis of atmospheric air pollution at the present stage was carried out from the point of view of preserving nature and civilization.